Study of Lung Cancer Hazard Due to Radiate Radon Gas for Two Factories in Industrial Region (Shaikh Omar) of Baghdad Governorate - Mohammed, N. A.; Ebrahiem, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
During the winter, in the industry region (Shaikh Omer) and by applying a passive radon detector (CR-39), lung cancer risk has been measured in twelve rooms of different workshops of two old factories in this site. The radon concentration is ranged from (123.345 Bq/m3) to (328.985 Bq/m3) with an average of (244.19Â±61.52 Bq/m3). Lung cancer risk ranged from 55.993 to 149.346 per million people and with an average of (110.855 per million people) which were lower than the recommended values (170-230 per million people), so there was no cancer risk on workers in these locations.